Understanding Neonatal Death in Urban Area in Indonesia (Medico Legal Update, 2020)
Data collected by WHO from various countries found that in 2018, 47% of all under-five deaths occurred inthe neonatal period. The study aimed to analyze variables related to neonatal death in urban Indonesia. Theanalysis utilizes secondary data from the 2017 Indonesia Demographic and Health Survey. With stratificationand multistage random sampling, 17,265 women aged 15-49 years in urban areas with live births in the last 5years were sampled. Data were analyzed using a Binary Logistic Regression test. The analysis found that therichest women were 0.602 times more likely to experience neonatal death than the poorest women in urbanareas(OR 0.602; 95% CI 0.409-0.886). Primiparous women were 0.526 times more likely to experienceneonatal death than grand-multiparous women in urban areas of Indonesia(OR 0.526; 95% CI 0.307-0.903).Multiparous women were 0.636 times more likely to experience neonatal death than grand-multiparouswomen in urban areas in Indonesia(OR 0.636; 95% CI 0.492-0.822). Women who have antental care visits? 4 times have a 0.237 chance of experiencing neonatal death compared to women who have antental carevisits